ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA FAKULTAS EKONOMI UNIVERSITAS PGRI PALEMBANG - Edduar Hendri (Universitas PGRI Palembang, 2013)
The problem in this study is whether the quality of work , quantity of work and attitudes affect the performance of the employees at the Faculty of Economics, University of PGRI Palembang? The population in this study were all permanent employees of the Faculty of Economics, University of Palembang PGRI totaling 31 people and at the same time as the sample is taken . The data analysis technique used is multiple linear regression using SPSS 20.0 for Windows. The results showed that simultaneous variable quality of work , quantity of work and attitude together positive and significant effect on the performance of employees at the Faculty of Economics, University of PGRI Palembang . It can be seen from the value of F ( 8.962 ) is greater than F table (2.960) with probability significancy (0,000) smaller 0.05 ( α = 5 % ) and partially also a positive and significant effect of the quality of work, quantity of work and attitude towards the performance of employees at the Faculty of Economics, University of PGRI Palembang which produces greater tcount ttable with a probability value of less than 0.05 can be stated that the variable quality of work , quantity of work and attitude has a positive and significant influence on employee performance variables on Faculty Economics, University of PGRI Palembang. Keywords : Quality of work , quantity of work , attitude and performance of employees